Comparison of angiography-guided vs. intra-vascular imaging-guiding percutaneous coronary intervention of acute myocardial infarction: a real world clinical practice - Lin, Ting-Yu; Chen, Ying-Ying; Huang, Shao-Sung; Wu, Cheng-Hsueh; Chen, Li-Wei; Cheng, Yu-Lun; Hau, William K.; Hsueh, Chien-Hung; Chuang, Ming-Ju; Huang, Wei-Chieh; Lu, Tse-Min (Frontiers in Cardiovascular Medicine, 2024)
Background The role of routine intravascular imaging in percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) remains unclear. This study evaluated the clinical outcomes of PCI guided by different imaging modalities in AMI patients. Materials and methods Data from AMI patients who had undergone PCI between 2012 and 2022 were analyzed. The mean follow-up was 12.9 ± 1.73 months. The imaging modality-either intravascular ultrasound (IVUS), optical coherence tomography (OCT), or angiography alone-was selected at the operator's discretion. The primary endpoint was major adverse cardiac events (MACEs), including cardiovascular (CV) death, myocardial infarction (MI), target vessel revascularization. Results Of the 1,304 PCIs performed, 47.5% (n = 620) were guided by angiography alone, 37.0% (n = 483) by IVUS, and 15.4% (n = 201) by OCT. PCI guided by intravascular imaging modalities was associated with lower 1-year rates of MI (1.3%, P = 0.001) and MACE (5.2%, P = 0.036). OCT-guided PCI was linked to lower rates of 1-year CV death (IVUS vs. OCT: 6.2% vs. 1.5%, P = 0.016) and MACE (IVUS vs. OCT: 6.4% vs. 2.5%, P = 0.032). Intravascular imaging modalities and diabetes were identified as predictors of better and worse 1-year MACE outcomes, respectively. Conclusion PCI guided by intravascular imaging modalities resulted in improved 1-year clinical outcomes compared to angiography-guided PCI alone in AMI patients. OCT-guided PCI was associated with lower 1-year MACE rates compared to IVUS-guided PCI. Therefore, intravascular imaging should be recommended for PCI in AMI, with OCT being particularly considered when appropriate.